(untitled) (National Administration Journal, 2021)
Cash management is simply defined as making the right amount of money available at the right time and the right place to meet the government’s obligations in the most cost-effective way. The main features of modern cash management are centralized government bank accounts and establishment of a Treasury Single Account, ability to make accurate cash flow forecasts, use of short-term financing instruments, and capacity for the investment of excess cash reserves. Establishing a sound cash management framework with the mentioned features is beneficial not only to the governments and public entities, but also to other stakeholders including the beneficiaries of government payments, banks and lenders. Given the recent COVID-19 (coronavirus) pandemic and locked-down measures introduced in many countries, governments had to deal with unanticipated revenue decreases, and significantly increased public expenditures due to fiscal stimulus packages and pandemic related health expenditures. Therefore, existence of a well-structured government cash management is now even more important than before. This paper aims to explore cash flow forecasting and cash management practices in 24 countries in various regions, at different income levels and technical capacity, and alignment to good practices based on the information provided at the World Bank workshops on Cash Flow Forecasting and Cash Management held in 2018 and 2019. The paper also draws on experiences and practices from other emerging and advanced countries. Cases from different countries indicate that full implementation of modern cash management is still a challenge, even though the Treasury Single Account system is common in most countries and liquidity buffers were established or increased following the Global Financial Crisis. Cash flow forecasting is an area to improve given the accuracy, horizon and frequency of the projections are frequently limited. Fragmented institutional structure makes cash management even more challenging. Country cases also demonstrate that there is a significant room to strengthen coordination between debt and cash management and the use of short-term instruments to cover cash shortages. Investment of cash balances seems to be a bigger weakness as many countries keep their liquidity buffers in the Central Bank with no remuneration.